INVESTIGATION OF THE GENETIC ALTERATIONS IN CDKN2A/B AND IL7R IN T-CELL ACUTE LYMPHOBLASTIC LEUKEMIA - RMB Lemos; ES Costa; T Ferraz; MT Schramm; MM Lins; MCN Fagundes; ALT Maciel; M Emerenciano (Hematology, Transfusion and Cell Therapy, 2024)
T-cell acute lymphoblastic leukemia (T-ALL) is an aggressive hematopoietic disorder triggered by the acquisition of molecular alterations that affect thymocytes in early stages of its development. Deletions in CDKN2A/B are found in ̃65-70% of cases. However, their prognostic value is still undefined. Loss of CDKN2A, in addition to IL7R activation, contributes to the development of B-cell precursor ALL (B-ALL). The activation of IL7R, either due to the presence of gain-of-function mutations (̃10% of cases) or its upregulation, is a recurrent event in T-ALL associated with disease relapse. Thus, IL7R activation is a crucial event in T-ALL initiation, but its transcriptional profile and prognostic role are still unclear. We aimed to investigate the presence of molecular alterations in CDKN2A/B and in IL7R in samples from pediatric and adult patients diagnosed with T-ALL. Samples from patients with a morphological and immunophenotypic diagnosis of T-ALL between the years 2018-2023 from the INCA Hematology Service and different cancer treatment centers in Brazil were included. The SALSA MLPA P335-C1 kit (MRC Holland), multiplex ligation-dependent probe amplification (MLPA) technique, was used to evaluate the presence of copy number alterations (CNA) in genes related to lymphopoiesis and commonly altered in ALLs, such as CDKN2A/B. The presence of mutations/single nucleotide polymorphism (SNP) in IL7R was assessed by polymerase chain reaction (PCR) for amplification of exon 6 followed by ABI3500 sanger sequencing. The transcriptional levels of IL7R were investigated using real-time quantitative PCR (RT-qPCR). 38 T-ALL samples were included (13 female and 25 male individuals), whose median age was 11.5 years. CDKN2A/B deletions were observed in 16 pediatric (44.4%, being 8 monoallelic and 8 biallelic deletions) and 2 adults (5.6%, 1 monoallelic and 1 biallelic deletions). Activating indel mutations in IL7R, which affect the juxtamembrane region of the protein, were found in 2 pediatric patients. Both patients had high leukocyte counts (> 100 × 109 cells/mL) at diagnosis and presented concomitant CDKN2A/B biallelic deletions. Besides, we found that 36.8% of our cohort presented a single nucleotide polymorphism (SNP) rs6897932 in exon 6 of IL7R. Among these samples, 12/14 were pediatric and 2/14 adults. In the pediatric subset, 7 samples presented heterozygous (TC) and 5 homozygous variants (TT). Both adult samples had heterozygous genotype (TC). Our data corroborates the literature showing that CDKN2A/B genetic alterations are frequently found in T-ALL patients. The analysis of the mutation or SNP on the IL7R expression is undergoing. However, the two patients harboring IL7R activating mutations did not present transcriptional deregulation in this gene. Since it's still unclear whether the mutations lead to increased gene expression in our series of cases, we aim to explore other transcriptional pathways that might play a role in IL7R deregulation scenario in T-ALL. Of note, to the best of our knowledge, this is the first study describing a high frequency of the SNP rs6897932 in T-ALL.